Biomass combustion and potential health effects in the developing countries - Joshi, SK; Dahl, A; Kristensen, T; Roldin, P (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v8i2.3575 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 276-280